The Effect of Quercetin on Ovary Functions in Rats with Cyclophosphamide Induced Ovary Damage - Ceren Yildiz Eren; Hulusi Goktug Gurer; Ozlem Ozgur Gursoy; Oktay Yilmaz; Ece Tunc; Serap Unubol Aypak; Gamze Sevri Ekren Asici (IMR Press, 2024)
Background: Premature ovarian failure describes women under 40 who usually present with amenorrhea, hypergonadotropic hypogonadism, and infertility. Quercetin is an antioxidant flavonol. Quercetin's oxidative, kinase and cell cycle inhibitor activities are known. Our study aimed to examine the efficacy of Quercetin on premature ovarian failure. Methods: Forty-eight regular-cycled adult female Wistar rats weighing 200 ± 40 grams, 10-12 weeks old, were used in the study. They were randomly divided into four groups with 12 animals. Four groups are Control, Cyclophosphamide, Cyclophosphamide + Quercetin (100 mg/kg) and Quercetin (100 mg/kg) groups. At the end of the experiment, the ovarian tissues were quickly removed. Follicles were counted to determine the ovarian reserve. Serum was extracted, and an Anti-Müllerian hormone analysis was performed. RT-PCR (reverse transcriptase-polymerase chain reaction) from ovarian tissue performed mRNA expression analysis of the Ddx4 gene. Results: As a result of Cyclophosphamide administration, it was determined that there was a decrease in both early-stage follicles and total follicles. This decrease was also statistically significant (p < 0.05). Anti-Müllerian hormone levels were significantly lower in the group given Cyclophosphamide (p < 0.01). On the histological examination, the number of early-stage and total follicles was significantly decreased in the Cyclophosphamide group compared to the control group, and those of the Cyclophosphamide + Quercetin were very close to that of the control group. Anti-Müllerian hormone (AMH) levels were also significantly lower in the Cyclophosphamide group compared to the control, but they were recovered to the level of the control group by Quercetin treatment. Conclusions: Our study may prove that Quercetin can protect ovarian function against Cyclophosphamide-induced ovarian damage.